Diversion Arrangements in the Juvenile Criminal Justice System in Indonesia Oriented to the Best Interests of Children and Justice - Walim (Jurnal Ilmiah Hukum dan Keadilan, 2026)
Children in conflict with the law require special protection through the application of diversion to shift the criminal justice process toward non-judicial resolution mechanisms. However, the implementation of diversion under Law Number 11 of 2012 in Indonesia has not been optimal, as it remains oriented toward imprisonment and is limited to certain categories of offenses, thereby failing to fully prioritize the best interests of the child. This study aims to analyze the challenges in the implementation of diversion, the limitations of the existing regulatory framework, and possible measures for its improvement within the juvenile justice system. The research employs a normative legal method combined with a juridical-empirical approach. The findings reveal weaknesses in the aspects of legal substance, legal structure, and legal culture. Therefore, regulatory reform is necessary to expand the application of diversion to all juvenile offenses, in line with restorative justice principles and the Convention on the Rights of the Child, while still ensuring justice for victims.